Transition from coals to renewable energy: Evidence from Indonesia - Mahpud Sujai; Riko Wahyudi; Nova Amalia Sakina (Asian Development Bank Institute (ADBI), 2023)
The energy sector's position as the second-largest contributor to Indonesia's total emissions underscores a critical environmental challenge. This concern is further compounded by the substantial carbon footprint attributed to coal-based power plants. As a result, the energy sector has been included in an updated Indonesian Nationally Determined Contribution (NDC) to reduce 314 million metric tons CO2eq by 2030. The energy transition program in the subsector of electricity power plants, shifting from non-renewable fossil fuels to sustainable renewable sources, is one of the programs that will play a significant role in reducing emissions. However, the transition to renewable energy will necessitate numerous synergistic efforts in policy, technical, and financial arenas. This paper qualitatively identifies challenges and constraints of Indonesia's energy transition mechanism from four aspects: national energy planning; regulatory and legal framework; technology and infrastructure; and renewable energy financing. The study exposes diverse challenges, highlighting the complexity that characterizes the transition process and the need for a holistic approach, where policy decisions are seamlessly integrated with technological advancements and bolstered by robust financial support. This holistic approach will give information about the strategic decision-making by dissecting the intricacies of the energy transition, incentivizing renewable energy adoption through financial mechanisms, recalibrating regional structures, and instituting organizational reforms, paving pragmatic paths forward.
Keywords: P48; 330; energy; NDC; coal-fired power plant; renewable energy; energy transition